Impact of food, alcohol and pH on modified-release hydrocortisone developed to treat congenital adrenal hyperplasia. Issue 4 (April 2017) - Karunasena, Nayananjani; Margetson, Daniel N; Neal, Greg; Whitaker, Martin J; Ross, Richard JM
Abstract : Background: We developed a modified-release hydrocortisone, Chronocort, to replace the cortisol rhythm in patients with congenital adrenal hyperplasia. Food, alcohol and pH affect drug absorption, and it is important to assess their impact when replicating a physiological rhythm. Subjects and methods: In vitro dissolution to study impact of alcohol and pH on Chronocort. A phase 1, three-period, cross over study in 18 volunteers to assess the impact of food on Chronocort and to compare bioavailability to immediate-release hydrocortisone. Results: In vitro dissolution of Chronocort was not affected by gastrointestinal pH up to 6.0 nor by an alcohol content up to 20% v/v. Food delayed and reduced the rate of absorption of Chronocort as reflected by a longer Tmax (fed vs fasted: 6.75 h vs 4.5 h, P = 0005) and lower Cmax (549.49 nmol/L vs 708.46 nmol/L, ratio 77% with CI 71–85). Cortisol exposure was similar in fed and fasted state: Geo LSmean ratio (CI) AUC0t for fed/fasted was 108.33% (102.30–114.72%). Cortisol exposure was higher for Chronocort compared to immediate-release hydrocortisone: Geo LSmean ratios (CI) 118.83% (111.58–126.54%); however, derived free cortisol showed cortisol exposure CIs were within 80.0–125.0%: Geo LSmean ratio (CI) for AUC0t 112.73% (105.33–120.65%). Conclusions: Gastric pH ≤6.0 and alcohol do not affect hydrocortisone release from Chronocort. Food delays Chronocort absorption, but cortisol exposure is similar in the fasted and fed state and exposure as assessed by free cortisol is similar between Chronocort and immediate-release hydrocortisone.